Archives and the Australian Great War centenary: retrospect and prospect - Michael Piggott (Archives & Manuscripts, 2020)
Based on a keynote address to the 2018 International Society for First World War Studies conference, the author’s survey of a centenary of archival endeavour comprises four time periods and two themes. It highlights the unique role of the Australian War Memorial and its initial documentation priorities favouring Dr C.E.W. Bean’s official war history, the battlefront and the war dead. A post-centenary open-ended aftermath is also discussed covering processing backlogs, the prospective idea of ‘digital breakthrough’ and the archival implications of ever-widening understandings of the war and its endless aftermaths. The paper ends with an appeal for new voices in researching the documentation of Australia’s Great War experience.